Additive Manufacturing of Polymer/Mg-Based Composites for Porous Tissue Scaffolds - Fawad Ali (2154529) (2022)
Due to their commercial availability, superior processability, and biocompatibility, polymers are frequently used to build three-dimensional (3D) porous scaffolds. The main issues limiting the widespread clinical use of monophasic polymer scaffolds in the bone healing process are their inadequate mechanical strength and inappropriate biodegradation. Due to their mechanical strength and biocompatibility, metal-based scaffolds have been used for various bone regenerative applications. However, due to the mismatch in mechanical properties and nondegradability, they lack integration with the host tissues, resulting in the production of fiber tissue and the release of toxic ions, posing a risk to the durability of scaffolds. Due to their natural degradability in the body, Mg and its alloys increasingly attract attention for orthopedic and cardiovascular applications. Incorporating Mg micro-nano-scale particles into biodegradable polymers dramatically improves scaffolds and implants’ strength, biocompatibility, and biodegradability. Polymer biodegradable implants also improve the quality of life, particularly for an aging society, by eliminating the secondary surgery often needed to remove permanent implants and significantly reducing healthcare costs. This paper reviews the suitability of various biodegradable polymer/Mg composites for bone tissue scaffolds and then summarizes the current status and challenges of polymer/magnesium composite scaffolds. In addition, this paper reviews the potential use of 3D printing, which has a unique design capability for developing complex structures with fewer material waste at a faster rate, and with a personalized and on-site fabrication possibility. Other Information Published in: Polymers License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/polym14245460